A newton method for the reconstruction of perfectly conducting slightly rough surface profiles - Yapar, A; Özdemir, Ö; Sahintürk, H; Akduman, I (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2006)
A new method for the reconstruction of a one-dimensional profile of a perfectly conducting rough surface illuminated by a plane wave at a fixed frequency is addressed. By a special representation of the scattered electric field, the total field in the half-space over the surface is obtained from the measured data, which leads to a nonlinear equation with a surface function as unknown. The nonlinear equation is solved iteratively via the Newton method and a regularization in the least square sense. Numerical simulations show that the method yields satisfactory reconstructions for slightly rough surface profiles.
Keywords: inverse scattering; Newton's method; rough surface; SCATTERING; FIELD; Engineering; Telecommunications